Carica Fruit Processed Distribution Strategy To Increase Sales Volume of Micro Small and Medium Enterprises at Kejajar District, Wonosobo Regency - Nasiron Nasiron; Suhendar Sulaeman; Liza Nora (School of Business, IPB University (SB-IPB), 2022)
Kejajar District, Wonosobo Regency, is a producer of Carica papaya in 2021 with a harvested area of 67,473 trees with a total production of 119.98 quintals with an average productivity value of 1.78 quintals per tree. The purpose of this research is to conceptualize and determine the choice of distribution criteria that can increase sales of processed carica fruit to increase sales volume. The method used is a case study approach combined with the Composite Performance Index (CPI) with 10 informants as resource persons. The results found are farmer cooperation and developing the main criteria by collaborating with experienced private sector. It can be concluded that the main distribution priority is to increase the quality and quantity of raw material products, namely collaborating with carica farmers which are then combined with collaboration with experienced private companies so that it will increase the sales volume of processed carica fruit in Micro, Small and Medium Enterprises (MSMEs) in Kejajar District, Wonosobo Regency in the future. Keywords: carica fruit, distribution strategy, carica wonosobo, case study, CPI